Assessing the efficacy of 10% oral dextrose in reducing pain in infants during venipuncture: A randomized controlled clinical trial - Leila Barati; Sajjad Khatami; Mitra Valizadeh; Homeira Khoddam (Golestan University of Medical Sciences, 2023)
Background: Available evidence on the efficacy of sweet solutions for reducing pain in infants is insufficient. This study aimed to assess the effects of 10% oral dextrose on the pain of infants during venipuncture. Methods: This randomized controlled clinical trial was done on 60 infants undergoing venipuncture. Eligible infants were randomly assigned into an intervention and control group. Two minutes before venipuncture, 2 ml of 10% oral dextrose solution and 2 ml of water were given to the intervention and control groups, respectively. The infants' pain intensity during the procedure was measured by two independent experts based on the Face, Legs, Activity, Cry, and CONSOL ability Behavioral Pain Scale. Data were analyzed using independent t-test and ANOVA tests. A P-value of ≤0.05 was considered statistically significant. Results: The mean (±standard deviation) age of infants in the intervention and control groups were 6.37 (2.96) and 9.03 (3.10) months, respectively (P0.05). In addition, the standardized mean difference in pain score between the two groups was -0.2 (95% confidence interval: -0.30 to 0.71). Despite a significant difference (P=0.003) in the pain score between females and males, the effect of intervention after gender effect correction was not statistically significant. Conclusion: Using 2 ml of 10% oral dextrose 2 minutes before venipuncture has a weak and non-significant effect on the pain of infants. Based on the effect size and 95% confidence interval, conducting further trials with a larger study population is recommended.